Evidence-based clinical decision making during the COVID-19 pandemic - Taype-Rondan, Alvaro (2020)
The COVID-19 pandemic is a difficult scenario for clinical decision making. Therefore, this paper aims to explain healthcare practitioners some basic concepts about evidence-based decision making with respect on doing or not doing a given intervention. For this, firstly we will discuss in which cases an evidence-based decision making process in necessary. Then, some previous concepts will be clarified (decision making based on pathophysiological plausibility, observations made during clinical practice, clinical evidence, as well as the influence from the pharmaceutical industry). Afterwards steps for evidence-based decision making will be described: Asking a question, looking for references answering this question, critically assess such references, understand the underlying logic for decision making, prepare for decisionmaking, make a balance (benefit, harm, and cost), perform a shared decision making process and reassess the evidence.